DEVELOPMENT OF IONIC LIQUID NANOCOMPOSITE MEMBRANES (ILNCMS) FOR CO2/CH4 SEPARATION - MANNAN, HAFIZ ABDUL (2018)
Membrane technology has a potential to be used for CO2-rich offshore applications. However, mixed matrix membranes suffer from both interfacial defects and permeability-selectivity tradeoff.